2017
DOI: 10.1093/hmg/ddx384
|View full text |Cite
|
Sign up to set email alerts
|

Ciliogenesis and cell cycle alterations contribute to KIF2A-related malformations of cortical development

Abstract: Genetic findings reported by our group and others showed that de novo missense variants in the KIF2A gene underlie malformations of brain development called pachygyria and microcephaly. Though KIF2A is known as member of the Kinesin-13 family involved in the regulation of microtubule end dynamics through its ATP dependent MT-depolymerase activity, how KIF2A variants lead to brain malformations is still largely unknown. Using cellular and in utero electroporation approaches, we show here that KIF2A disease-caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 55 publications
3
45
0
Order By: Relevance
“…As expected, approximately 45% of tdTomato-positive neurons had reached the CP, 50% were migrating along the SVZ-IZ region and 5% were localized to the VZ in control samples at three days postelectroporation ( Fig.3A). Consistent with previous observations 20,21 , there was a dramatic reduction in the relative fraction of tdTomato-positive neurons localized to the CP in Kif2a knockdown samples, and deficient migration caused most of the neurons to accumulate in the SVZ-IZ (Fig.3A). In cortices where Kif2a expression was rescued with either resKIF2A.1 or resKIF2A.2, neurons could exit the SVZ-IZ and reach the CP, at levels comparable to control samples ( Fig.3C, D, F and G).…”
Section: Specific Kif2a Isoforms Appear To Play a Role In Radial Migrsupporting
confidence: 91%
See 1 more Smart Citation
“…As expected, approximately 45% of tdTomato-positive neurons had reached the CP, 50% were migrating along the SVZ-IZ region and 5% were localized to the VZ in control samples at three days postelectroporation ( Fig.3A). Consistent with previous observations 20,21 , there was a dramatic reduction in the relative fraction of tdTomato-positive neurons localized to the CP in Kif2a knockdown samples, and deficient migration caused most of the neurons to accumulate in the SVZ-IZ (Fig.3A). In cortices where Kif2a expression was rescued with either resKIF2A.1 or resKIF2A.2, neurons could exit the SVZ-IZ and reach the CP, at levels comparable to control samples ( Fig.3C, D, F and G).…”
Section: Specific Kif2a Isoforms Appear To Play a Role In Radial Migrsupporting
confidence: 91%
“…In addition, previous studies have shown that the KIF2A H321D mutation is causal for migration defects in humans and mice 20,22 . Interestingly, we have noticed that the interactomes of KIF2A.3 and KIF2A H321D display a considerable number of common targets not identified in our KIF2A.1 and KIF2A.2 interactome datasets.…”
Section: Discussionmentioning
confidence: 97%
“…As a consequence, cell cycle (G 1 /S transition) is delayed, leading to the premature switch of progenitors from a proliferative to a differentiating state [Gabriel et al., ]. Similar observations were initially made for Tctex‐1 (or DNYLT1), a dynein‐associated protein which negatively regulates ciliary disassembly [Li et al., ], NDE1 [Kim et al., ; Doobin et al., ], a partner of CPAP involved in severe forms of microcephaly [Alkuraya et al., ; Bakircioglu et al., ], and more recently for KIF2A [Broix et al., ], a kinesin involved in ciliary disassembly upon cell‐cycle reentry [Miyamoto et al., ] for which mutations were identified in MCD cases [Poirier et al., ; Cavallin et al., ].…”
Section: Could Microcephaly Be Regarded As a Ciliopathy‐associated Phmentioning
confidence: 71%
“…KIF2A was shown to be involved in the disassembly of cilia upon cell cycle entry through a PLK1‐mediated activation of its depolymerising activity [Miyamoto et al ., ]. Loss of Kif2A in mice leads to severe brain defects and dominant KIF2A mutations in humans lead to microcephaly [Poirier et al ., ], due, at least partially, to the cell cycle delay in neuron progenitors resulting from cilia disassembly defects [Broix et al ., ]. Intriguingly, besides brain anomalies, loss of Kif2A in mouse does not lead to obvious ciliopathy phenotypes, suggesting that its role in ciliary disassembly might be brain specific.…”
Section: Pc‐specific Kifmentioning
confidence: 99%